The immigrant earnings disadvantage across the earnings and skills distributions: The case of immigrants from the EU's new member states in Ireland - Alan Barrett; Séamus McGuiness; Martin O'Brien (The Economic and Social Research Institute (ESRI), 2008)
As the movement of population from the New Member States (NMS) of the EU to the older members is a relatively new flow, it is important to build up our knowledge of who is moving within Europe and how they are performing in their destinations. In this paper, we analyse the earnings of immigrants in Ireland from the NMS using a new large-scale dataset on employees in Ireland. In so doing, we add to the emerging strand in the literature on immigrant earnings that looks beyond average earnings differentials and considers variations in such differentials across the earnings and skills distributions. We do this partly by using quantile regressions and also by analyzing earnings differentials within educational categories. We find that the average earnings difference between immigrants from the NMS and natives is between 10 percent and 18 percent, depending on the controls used. However, the difference is found to be either non-existent or low for people with low skill levels and for people at the lower end of the earnings distribution. The difference is higher for those at the upper ends of the skills and earnings distributions. This suggests that the transferability of human capital is a crucial determinant of the immigrant-native earnings gap for NMS immigrants in Ireland.
Keywords: 330; immigrant earnings; Ireland; New Member States; quantile regression; Internationale Arbeitsmobilität; Einwanderung; Ausländische Arbeitskräfte; Qualifikation; Einkommen; EU-Erweiterung; Irland